As toadas de bumba meu boi no maranhão e a formação discursiva da tradição popular maranhense - NASCIMENTO, Fagner Gomes do (2023)
The conception of the principle of cultural citizenship foresees that society seeks the recognition and appreciation of cultural goods that have the historical and citizenship exteriorization of a certain people. This work approach the history, symbolism and cultural diversity of Bumba meu boi in the State of Maranhão, with a discursive analysis of the contribution of Bumba meu Boi’s songs to the discursive formation of the popular tradition of Maranhão. In this scenario, it is worth asking the following question: how did the effects of meaning occur through the discursive formations of Bumba meu boi’s songs constitute the imaginary of Maranhão's popular tradition? We intend to analyze how the effects of meaning of Bumba meu boi’s songs constitute the imaginary formation of Maranhão popular tradition, approaching the enunciated speeches and their regularities. Through a bibliographic basis gathered from undergraduate research, articles, periodicals and books related to the subject, it will be presented in this academic work, in which the corpus of the discourse analysis will be Bumba meu boi’s songs, in which the research was discursive in nature , qualitative and indicative, which contributed to the development of the discursive formation of the popular tradition of Maranhão. As a result of this work, it can be pointed out that the Bumba meu boi’s songs have the effect of creating and preserving the good and the artistic, historical, social, cultural values, among others, all inside the activity of Bumba meu boi. It is concluded that the songs through the textual-discursive aspects favor the construction of the identity of Bumba meu boi da Maioba, in order to obtain a better understanding of the discursive identity, as a popular cultural manifestation and discursive practice. Using the French Discourse Analysis as an analysis methodology, we are based mainly on the studies of Michel Pêcheux (2017), as well as those of his precursors in Brazil, from 1980 onwards, such as Eni Orlandi (2017) and Foucault ( 1971).